Intensive Care Unit Sedation Practices at a Large, Tertiary Academic Center. (October 2022) - Hofer, Mikaela M.; Wieruszewski, Patrick M.; Nei, Scott D.; Mara, Kristin; Smischney, Nathan J.
Background: Sedatives are frequently administered in an ICU and are often dependent on patient population and ICU type. These differences may affect patient-centered outcomes. Objective: Our primary objective was to identify differences in sedation practice among three different ICU types at an academic medical center. Methods: This was a retrospective cross-sectional study of adult patients (≥18 years) requiring a continuous sedative for ≥6 h and admitted to a medical ICU, surgical ICU, and medical/surgical ICU at a single academic medical center in Rochester Minnesota from June 1, 2018 to May 31, 2020. We extracted baseline characteristics; sedative type, dose, and duration; concomitant therapies; and patient outcomes. Summary statistics are presented. Results: A total of 2154 patients met our study criteria (1010 from medical ICU, 539 from surgical ICU, 605 from medical/surgical ICU). Propofol was the most frequently used sedative in all ICU settings (74.1% in medical ICU, 53.8% in surgical ICU, 68.9% in medical/surgical ICU, and 67.5% in all ICUs). The mortality rate was highest in the medical/surgical ICU (40.2% in medical ICU, 26.0% in surgical ICU, 40.7% in medical/surgical ICU, and 36.8% in all ICUs). 90.7% of all patients required mechanical ventilation (92.9% in medical ICU, 88.5% in surgical ICU, and 89.1% in medical/surgical ICU). Overall, patients spent more time in light sedation than deep sedation, 75% versus 10.3%, during their ICU admission. Patients in the medical ICU spent a greater proportion of time positive for delirium than the other ICU settings (35.7% in medical ICU, 9.8% in surgical ICU, and 20% in medical/surgical ICU). Similar amounts of opioids (morphine milligram equivalents) were used during the continuous sedative infusion between the three settings. Conclusions: We observed that patients in the medical ICU spent more time deeply sedated with multiple agents which was associated with a higher proportion of delirium.